2018
DOI: 10.5380/rf.v48i2.56195
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Forwarder Productivity and Costs in Thinned Pine Stands

Abstract: The aim of this study was to assess the influence of some operational variables on the forwarder productivity and production cost in thinned Pinus taeda L. stands by means of mathematical modeling. This study was carried out in a forest company located at Quedas do Iguaçu, state of Paraná, Brazil. Two stands at 9 and 10 years old from sites with high productivity and similar soil and relief features were studied. A time-motion study was applied to determine the operational cycle time, operational efficiency, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
2
2
0
Order By: Relevance
“…In this way, it can be stated that the forwarder spends more time in the cycle operating passively, either by loading or unloading wood. These results corroborate with the results of several authors such as Simões and Fenner (2010), Lopes et al (2016), and Rodrigues et al (2018), who studied this machine in different situations regarding forest species and management regime. However, it is noteworthy that the time consumed in the loading described above tends to increase due to the difficulties of executing the operation inside the stand, and considering the precautions taken regarding damage to the remaining trees.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this way, it can be stated that the forwarder spends more time in the cycle operating passively, either by loading or unloading wood. These results corroborate with the results of several authors such as Simões and Fenner (2010), Lopes et al (2016), and Rodrigues et al (2018), who studied this machine in different situations regarding forest species and management regime. However, it is noteworthy that the time consumed in the loading described above tends to increase due to the difficulties of executing the operation inside the stand, and considering the precautions taken regarding damage to the remaining trees.…”
Section: Discussionsupporting
confidence: 91%
“…usually removed in selective thinning (Lopes et al 2016, Acuña et al 2018, Cabral et al 2018, Rodrigues et al 2018.…”
mentioning
confidence: 99%
“…In analyzing the forwarder behavior, loading was the partial working cycle element which consumed the longest time, followed by wood unloading. This result is a behavior expected by the forwarder, since it spends most of its time in passive form, loading and unloading as already mentioned by Rodrigues et al (2018a). However, an increase in the woodpile volume in the excess working range was evident in T2 when the effect of working ranges on the machine's working cycle was evaluated.…”
Section: Discussionsupporting
confidence: 72%
“…h -¹ for 6m. In studying the forwarder extraction operation, Rodrigues et al (2018) concluded that the loading time was the element which consumed most of the operational cycle time, and its productivity increased as the volume per tree increased and the average distance of extraction decreased.…”
Section: Productivity Measurementmentioning
confidence: 99%